A mechanics principle based inverse technique for real-time monitoring of wear-level of contact wire in pantograph-catenary systems. Issue 1 (2nd January 2022) - Xu, F. T.; Duan, S. Y.; Wang, F.; Liu, G. R.
Abstract : In advanced railway systems, electricity is supplied to train through sliding contact of pantograph and power-transmission catenary, which causes continuous wear of transmission wire in pantograph-catenary system (PCS). It is of crucial to monitor wear to ensure the safety and smooth operations of electric trains in terms of precision and efficiency in services. This work has developed a novel inverse procedure that uses measurable mechanical quantities to predict and monitor contact wire wear regardless of whether pantograph passes. The inverse technique is based on rigorous mechanics principle and verified by numerical simulation. Three-dimensional (3D) finite element models (FEM) of PCS is first established to simulate both static mechanics behavior and dynamic contact process during sliding. A useful relationship between wear-level and displacement or contact force has been established through static studies. Intensive nonlinear dynamic contact analysis of PCS is then performed and found that the wear-level relates strongly to displacement variation of collector head, so as to devise an inverse procedure between those two when the train is running. In addition, simple formulae are derived by curve-fitting to estimate wire-level based on either static or dynamic measurements, for easy real-time applications of the results from our 3D FEM study.